2018
DOI: 10.1002/ece3.4029
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intestinal microbiota across an altitudinal gradient in the lizard Phrynocephalus vlangalii

Abstract: High altitude is an important driving force in animal evolution. However, the effect of altitude on gut microbial communities in reptiles has not been examined in detail. Here, we investigated the intestinal microbiota of three populations of the lizard Phrynocephalus vlangalii living at different altitudes using 16S rRNA gene sequencing. Bacteroidetes, Firmicutes, and Proteobacteria were the most abundant phyla. Bacteroides, Odoribacter, and Parabacteroides were the most abundant genera. Significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
95
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(109 citation statements)
references
References 38 publications
13
95
1
Order By: Relevance
“…In general, the vertebrates' gastrointestinal tract harbors a similar and conservative bacterial assemblage dominated by Firmicutes, Bacteroidetes, and Proteobacteria, with low relative abundances of other bacterial phyla [41]. The fecal microbiota of reptiles, such as herbivorous lizards, iguanas, and tortoises [42,43], the Burmese phyton (Python molurus) [44], and the lizards Phrynocephalus vlangalii [18], Liolaemus parvus, Liolaemus ruibali, and Phymaturus williamsi [45] are dominated also by Firmicutes and Bacteroidetes. However, it has been shown that the bacterial assemblages in the gut of squamates are affected by different parameters, such as diet, captivity, digestion of particular prey items, and periods of fasting [6,[45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, the vertebrates' gastrointestinal tract harbors a similar and conservative bacterial assemblage dominated by Firmicutes, Bacteroidetes, and Proteobacteria, with low relative abundances of other bacterial phyla [41]. The fecal microbiota of reptiles, such as herbivorous lizards, iguanas, and tortoises [42,43], the Burmese phyton (Python molurus) [44], and the lizards Phrynocephalus vlangalii [18], Liolaemus parvus, Liolaemus ruibali, and Phymaturus williamsi [45] are dominated also by Firmicutes and Bacteroidetes. However, it has been shown that the bacterial assemblages in the gut of squamates are affected by different parameters, such as diet, captivity, digestion of particular prey items, and periods of fasting [6,[45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that Oscillospira degrade glycans of the host, such as fucose, sialic acids, and glucuronic acid. As such, it is more likely that dietary restriction enrich members of Oscillospira living at 4150 m instead of low O 2 pressure and low temperature as suggested by Zhang et al [18]. Additionally, the lizards at this high altitude were exposed to longer periods of lower temperatures than those at lower altitude, which promotes long periods of inactivity and fasting [15].…”
Section: Composition Of the Fecal Microbiota Of Sceloporus Grammicus mentioning
confidence: 93%
See 2 more Smart Citations
“…Taken together, these studies show that an increased abundance of specific gut microorganisms improves the overall digestibility of nutrients in mammals living at high altitude (Li et al, ; Zhang et al, ; Zhao et al, ). The effect of altitude on the gut microbiome has also been investigated in other vertebrates, such as Tibetan chickens (Zhou et al, ) and lizards (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%